2009
DOI: 10.1111/j.1365-2427.2008.02118.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of N : P loading ratios on phytoplankton community composition, primary production and N fixation in a eutrophic lake

Abstract: Summary 1. The aim of this study was to assess the effects of different nitrogen (N) to phosphorus (P) loading ratios on phytoplankton community composition and primary production in a naturally eutrophic lake. Furthermore, the sources of N fuelling primary production were estimated using 15N stable isotope tracers. 2. A mesocosm experiment was performed with the same amount of P added to all mesocosms (similar to internal loading rates) but with a range of N additions (0–86 μm N), resulting in a gradient of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
65
2
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(79 citation statements)
references
References 51 publications
6
65
2
4
Order By: Relevance
“…Previous studies have suggested that N-fixing cyanobacteria can outcompete non-N-fixing cyanobacteria only under sufficient P levels (Piehler et al 2009;Vahtera et al 2010). The concentration of SRP was 2À8 mg/L in the summer of 2014 in the Zhoucun Reservoir and may be inadequate for an N-fixing cyanobacteria bloom (Vrede et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that N-fixing cyanobacteria can outcompete non-N-fixing cyanobacteria only under sufficient P levels (Piehler et al 2009;Vahtera et al 2010). The concentration of SRP was 2À8 mg/L in the summer of 2014 in the Zhoucun Reservoir and may be inadequate for an N-fixing cyanobacteria bloom (Vrede et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…The changes in community composition in response to altered N-P availability by nitrogen enrichment can result from multiple processes. These are some reported examples: First, the N 2 -fixing community loses its competitive advantage over other species and decreases in abundance 39 . Second, increased N:P availability ratio in soils and waters favours the slow-growing species with high optimal N:P ratios at the expense of the fast-growing species with lower optimal N:P ratio 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that in areas with low atmospheric N deposition (such as at high latitudes) N strongly limits PPr, especially in unproductive lakes (Vitousek and Howarth 1991;Bergström and Jansson 2006;Elser et al 2009). In productive lakes N fixation by cyanobacteria can potentially compensate for N deficiency, as N-fixing cyanobacteria often become dominant at low N : P ratios, thus alleviating N limitation of PPr (Vrede et al 2009). However, in nutrient-rich lakes, N limitation is also common (Downing and McCauley 1992;Elser et al 2007), and in some cases N fixation may not totally compensate for N limitation of PPr (Scott and McCarthy 2010).…”
Section: Discussionmentioning
confidence: 99%